A comparison of functional magnetic resonance imaging findings in children with and without a history of early exposure to general anesthesia. Issue 3 (3rd January 2015) - Taghon, Thomas A.; Masunga, Abigail N.; Small, Robert H.; Kashou, Nasser H.; Anderson, Brian
Summary Background Functional magnetic resonance imaging (fMRI) has been used to evaluate the long‐term consequences of early exposure to neurotoxic agents. fMRI shows that different patterns of brain activation occur in ethanol‐exposed subjects performing a go/no‐go response inhibition task. Pharmacologically, ethanol and general anesthetics have similar receptor‐level activity in the brain. This study utilizes fMRI to examine brain activation patterns in children exposed to general anesthesia and surgery during early brain development. Methods After obtaining Nationwide Children's Hospital IRB approval, a surgical database was utilized to identify children aged 10–17 years with a history of at least 1 h of exposure to general anesthetics and surgery when they were between 0 and 24 months of age. Age‐ and gender‐matched children without anesthesia exposure were recruited as a control group. All subjects were scanned while being presented with a go/no‐go response inhibition task. Reaction time and accuracy data were acquired, and the blood‐oxygen‐level‐dependent (BOLD) fMRI signal was measured as a biomarker for regional neuronal activity. Results There were no differences in terms of performance accuracy and response time. The analysis did not reveal any significant activation differences in the primary region of interest (prefrontal cortex and caudate nucleus); however, activation differences were seen in other structures, including the cerebellum, cingulate gyrus, and paracentral lobule. Conclusions Early anesthetic exposure and surgery did not affect accuracy, response time, or activation patterns in the primary region of interest during performance of the task. Intergroup differences in activation patterns in other areas of the brain were observed, and the significance of these findings is unknown. fMRI appears to be a useful tool in evaluating the long‐term effects of early exposure to general anesthesia.